PENGEMBANGAN INSTRUMEN TES BERBASIS WORDWALL PADA MATERI ASAM BASA FASE F SMA/MA - Nabeta, Elputri; Syolendra, Dwi Finna (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
This study aims to develop a Wordwall-based test instrument on acid–base material for Phase F senior high school (SMA/MA) students and to determine the validity and practicality of the developed instrument. The development of technology-based test instruments is required in line with the implementation of the Merdeka Curriculum, which emphasizes the integration of digital technology in assessment, as well as the characteristics of Phase F students who belong to Generation Z and are accustomed to using digital technology. Acid–base material is one of the chemistry topics that is abstract in nature and therefore requires an assessment instrument capable of optimally measuring students’ conceptual and procedural understanding. This study employed an Educational Design Research (EDR) approach using the Plomp development model, which was limited to the stages of prototype development, validity testing, and practicality testing. The research instruments consisted of logical validity sheets, learning achievement tests, and practicality questionnaires. Logical validity was assessed by five experts, while empirical validity, reliability, item discrimination index, and difficulty index were used to determine the feasibility of the developed test items. Practicality testing was conducted through questionnaires administered to teachers and students. The results showed that the instrument obtained an Aiken’s V value of 0.90 and an empirical validity value of 0.91, both categorized as valid, with a reliability coefficient of 0.88, while the item discrimination and difficulty indices met the established criteria. The practicality test results showed percentages of 96% from teachers and 91% from students, both categorized as very practical. Therefore, the Wordwall-based test instrument on acid–base material for Phase F SMA/MA students is declared valid and practical for use as an assessment instrument. ABSTRAK Penelitian ini bertujuan untuk mengembangkan instrumen tes berbasis Wordwall pada materi asam-basa Fase F SMA/MA serta mengetahui tingkat validitas dan praktikalitas instrumen yang dikembangkan. Pengembangan instrumen tes berbasis teknologi digital diperlukan seiring dengan implementasi Kurikulum Merdeka yang menekankan pemanfaatan teknologi dalam asesmen serta karakteristik peserta didik Fase F yang tergolong Generasi Z dan terbiasa menggunakan teknologi digital. Materi asam-basa merupakan salah satu materi kimia yang bersifat abstrak sehingga memerlukan instrumen asesmen yang mampu mengukur pemahaman konseptual dan prosedural peserta didik secara optimal. Penelitian ini menggunakan pendekatan Educational Design Research (EDR) dengan model pengembangan Plomp yang dibatasi hingga tahap pengembangan prototipe, uji validitas, dan uji praktikalitas. Instrumen penelitian meliputi lembar validitas logis, tes hasil belajar, dan angket praktikalitas. Validitas logis dinilai oleh lima orang ahli, sedangkan validitas empiris, reliabilitas, daya beda, dan indeks kesukaran digunakan untuk menilai kelayakan butir soal. Uji praktikalitas dilakukan melalui angket kepada guru dan peserta didik. Hasil penelitian menunjukkan nilai Aiken’s V sebesar 0,90 dan validitas empiris sebesar 0,91 dengan kategori valid, reliabilitas sebesar 0,88, serta daya beda dan indeks kesukaran yang memenuhi kriteria. Uji praktikalitas memperoleh persentase sebesar 96% oleh guru dan 91% oleh peserta didik dengan kategori sangat praktis. Dengan demikian, instrumen tes berbasis wordwall pada materi asam–basa Fase F SMA/MA dinyatakan valid dan praktis untuk digunakan sebagai instrumen asesmen.